In silico characterization of adh1 gene encoding alcohol dehydrogenase 1 (ADH1) from non-conventional yeast, Wickerhamomyces and Pichia spp - HARTONO, FAISAL DINIAMAL; MERYANDINI, ANJA; ASTUTI, RIKA INDRI (Jurnal Natural, 2025)
Wickerhamomyces anomalus and Pichia kudriavzevii have high potential to produce bioethanol under high stress condition, due to their stress-tolerant properties. To elucidate and develop an efficient and sustainable bioethanol production, characterization of ethanol fermentation reactions is highly substantial. Ethanol fermentation employs key enzyme ADH1 encoded by ADH1 gene, important for conversion of acetaldehyde to ethanol. However, structural studies about alcohol dehydrogenase1 from these genera of yeasts are limited. This study aimed to detect the alcohol dehydrogenase 1 gene from Pichia spp. Using computational-bioinformatics approaches. The adh1 gene was amplified by PCR, visualized by electrophoresis, and analysed for sequence homology by BlastN and BlastP. The enzyme structure was constructed by SWISS-MODEL and I-TASSER with validation by Ramachandran plot, QMEAN4, and Local Quality Estimate. The Similarity and homology analysis of ADH1 genes and their corresponding protein sequence of yeast isolates showed that the ADH1gene was successfully detected. Multiple sequence alignment (MSA) and phylogenetic tree revealed that W. anomalus BT1-BT6 has close evolutionary relationship with ADH1 from Saccharomyces cerevisiae sequence while P. kudriavzevii IP4 showed different pattern. The ADH 1 enzyme model, generated using the SWISS-MODEL web server, demonstrated the best stereochemical quality, with a Ramachandran plot value of 100% for W. anomalus BT1 and 99.3% for P. kudriavzevii IP4. Superimposition of 3D-predicted model of ADH1 from W. anomalus BT1 and P. kudriavzevii 1P4 showed an exact match with amino acid in Zn2+ binding sites, confirming the ADH1 metaloenzyme properties. These findings provide structural insights about ADH1 genes and protein properties which can be used further for the development of efficient and high productivity of bioethanol productions through genetic and protein engineering.